Clinico-Pathological Association of Haemoglobin At The Time of Presentation: A Predictive Tool of Survivorship in COVID-19 - Warraich, Imran Samee; Khan, Irfan; Abid, Muhammad; Fatimah, Sarah; Irshad, Zareen; Hanif, Saima (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the clinico-pathological association of haemoglobin at the time of presentation as a predictor of survivorship in patients suffering from COVID-19. Study Design: Prospective observational study. Place and Duration of Study: Combined Military Hospital Hyderabad Pakistan, from Mar to Sep 2020. Methodology: Two hundred and four patients who were symptomatic and PCR positive for COVID-19 were included in the study. Informed consent was taken from patients and approval from the institutional ethics committee was obtained. Haemoglobin values were analyzed using SPSS version 22. Results: In our study, 186 (91.2%) patients survived the disease and 18 (8.8%) patients died. The mortality rate was high in patients who presented with low haemoglobin levels at time of presentation. Conclusion: This study concluded that hemoglobin level at time of presentation could be a predictor of survivorship.